Potensi Dan Pengembangan Mahakam Riverside Market Melalui Community-Based Tourism - Fitri, Lutviani Silvia; Astina, I Komang; Fahmi, Akmal; Fahmi, Akmal (JURNAL DESTINASI PARIWISATA; Vol 10 No 1 (2022): VOL 10, NO 1 (2022): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2022.v10.i01.p05, 2022)
The existence of Mahakam Riverside Market (MARIMAR) as a forum that aims to improve the economy in Samarinda City becomes a very interesting object and has the potential to become a new tourist attraction in Samarinda City. MARIMAR has had both positive and negative impacts on society. The resulting positive impacts include increasing the economy and public welfare. However, on the other hand, the opening of tourism like this certainly has a negative impact such as environmental damage, air pollution and a decrease in water and environmental quality. This study aims to analyze the Mahakam Riverside Market (MARIMAR) development strategy through community-based tourism (CBT). This research is a qualitative descriptive research with a naturalistic research design. The data analysis used is Tourism Component Analysis 4A and SWOT Analysis. The results of the analysis show that Mahakam Riverside Market (MARIMAR) has strong potential to be developed into a tourist area through local community empowerment (CBT). Empowerment of local communities can be done in 3 stages, namely enabling (capacity building), empowering, and protecting (maintaining). Keyword: Mahakam Riverside Market; community-based tourism; Mahakam River; Samarinda